Effects of Coupling between Lateral and Torsional Motions in Seismic Response of Buildings - Jarallah, Husain Khalaf (Basrah Journal for Engineering Sciences, 2018)
The goal of the present paper is to study the adequacy of torsional provisions in the international buildings code (IBC) for irregular building taken into account effect of the angles of seismic attacks. The responses of the frame-shear-wall twelve- story asymmetric building under earthquake loading by using equivalent lateral force procedure and dynamic response spectrum analysis have been studied intensively in this present research paper. This study performs static and dynamic response analyses of building models under earthquake ground motions compatible with the design response spectrum defined in the international buildings code. The dynamic response spectrum was scaled according to the code static base shear. The static and dynamic base shear with different angles of seismic attacks has been calculated. The scaling factors, angles of seismic attacks, accidental storey torsions, storey shear, dynamic and static base shear have been evaluated here. The torsional moment at different storey levels for dynamic analysis has been estimated and compared with the static values.